2014
DOI: 10.1371/journal.pone.0109938
|View full text |Cite
|
Sign up to set email alerts
|

Stimulators of Mineralization Limit the Invasive Phenotype of Human Osteosarcoma Cells by a Mechanism Involving Impaired Invadopodia Formation

Abstract: BackgroundOsteosarcoma (OS) is a highly aggressive bone cancer affecting children and young adults. Growing evidence connects the invasive potential of OS cells with their ability to form invadopodia (structures specialized in extracellular matrix proteolysis).ResultsIn this study, we tested the hypothesis that commonly used in vitro stimulators of mineralization limit the invadopodia formation in OS cells. Here we examined the invasive potential of human osteoblast-like cells (Saos-2) and osteolytic-like (143… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Additionally, there was an upregulated expression of PHEX and MEPE 9 both associated with decreased mineral production and differentiation into osteocytes. In contrast, Cmoch et al 7 observed increased mineralisation by Saos-2 cells at a similar β-Gly concentration. However, whilst many studies use β-Gly, some authors recommend avoiding the use of ~ 10 mM β-Gly as it causes non-physiological levels of extracellular phosphate that can alter normal osteogenic gene transcription 10 .…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Additionally, there was an upregulated expression of PHEX and MEPE 9 both associated with decreased mineral production and differentiation into osteocytes. In contrast, Cmoch et al 7 observed increased mineralisation by Saos-2 cells at a similar β-Gly concentration. However, whilst many studies use β-Gly, some authors recommend avoiding the use of ~ 10 mM β-Gly as it causes non-physiological levels of extracellular phosphate that can alter normal osteogenic gene transcription 10 .…”
Section: Introductionmentioning
confidence: 79%
“…Valenti et al 6 showed Asc-induced osteogenic differentiation at up to 250 µM with no signs of apoptosis below 750 µM in relatively undifferentiated osteoblast-like MG-63 cells. Whereas Cmoch et al 7 described activated matrix mineralisation accompanied by apoptosis in more fully differentiated Saos-2 cells exposed to 283 µM Asc and 7.5 mM β-Gly. The latter suggested a possible role of β-Gly in apoptosis which was not addressed by the authors.…”
Section: Introductionmentioning
confidence: 95%
“…ab139418) according to the manufacturer's instructions. Crystal violet staining and annexin V flow cytometry analyses were carried out as described before . For soft agar assay, we followed the protocol published online by Joseph Provost, University of San Diego, California, USA; link: http://home.sandiego.edu/~josephprovost/Research.html, accessed March 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Migration was assayed by wound healing experiments as previously described [ 63 ]. Time-lapse observations were performed for 48h using Leica AF7000 Live Imaging System (Leica Microsystems) microscope equipped with an environmental chamber, and a 10x/0.40NA objective.…”
Section: Methodsmentioning
confidence: 99%